Influence of Customer Experience, Brand Ambassador, and Perceived Value On Customer Loyalty Of Somethinc’s Consumer In Semarang - Rifani, Athaya Aurellia; Rustono, Rustono -; Suroija, Noor - (Politeknik Negeri Semarang, 2024)
This research aims to understand the influence of Customer Experience, Brand Ambassador, and Perceived Value on Customer Loyalty among consumers of Somethinc products in Semarang City. The sampling technique used purposive sampling totaling 120 samples. The analytical methods used include validity testing, reliability testing, descriptive analysis, normality testing, linearity testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression analysis, F testing, T testing, and coefficient of determination using SPSS version 25. Based on calculations that have been carried out, the results of the F test were obtained which showed a calculated F value of 77.461, exceeding the F table of 3.92. The results of the T test show that the calculated t score exceeds the T table and produces a significance score that does not exceed 0.05. The results of the coefficient of determination between the Customer Experience, Brand Ambassador and Perceived Value variables towards Customer Loyalty contributed 65.80%. The results of all the calculations above show that Customer Experience, Brand Ambassador, and Perceived Value have a significant impact on Customer Loyalty of Somethinc”™s consumer in Semarang